2012
DOI: 10.1109/jstars.2012.2196758
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Link InSAR Time Series: Enhancement of a Wrapped Interferometric Database

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…The dates inducing strong atmospheric effects were determined using pairwise logic [ Massonnet and Feigl , ]. For example, for track 213, we found that the tropospheric effects on 15 July 2008 strongly affected the radar wave propagation time as all interferograms using this date were affected whereas interferograms without this date were not affected [ Pinel‐Puysségur et al , ]. Similar analysis shows that significant atmospheric effects were also present on 19 August and 23 September 2008.…”
Section: Measuring the Ground Displacement With Insar: Methods And Resmentioning
confidence: 93%
See 1 more Smart Citation
“…The dates inducing strong atmospheric effects were determined using pairwise logic [ Massonnet and Feigl , ]. For example, for track 213, we found that the tropospheric effects on 15 July 2008 strongly affected the radar wave propagation time as all interferograms using this date were affected whereas interferograms without this date were not affected [ Pinel‐Puysségur et al , ]. Similar analysis shows that significant atmospheric effects were also present on 19 August and 23 September 2008.…”
Section: Measuring the Ground Displacement With Insar: Methods And Resmentioning
confidence: 93%
“…For track 363, 5 images yielded 8 interferograms and for track 213, 12 images yielded 31 interferograms. The database of wrapped interferograms was filtered using the Multilink SAR method [Pinel-Puysségur et al, 2012], which enhances the wrapped phase signal quality based on interferogram network redundancy. Black continuous lines are mapped faults [Kazmi, 1979;Nakata et al, 1991].…”
Section: Interferometric Processingmentioning
confidence: 99%
“…In order to evaluate the filtered interferograms without the high-resolution DEM ground truth of this area, we utilize the Colinearity Criterion proposed in [57], which is defined as:…”
Section: B Real Datamentioning
confidence: 99%
“…More recently, some new hybrid multi-temporal InSAR noise-filtering approaches, based on the joint exploitation of sequences of InSAR interferograms, have also been proposed [65][66][67][68].…”
Section: Noise Signals Corrupting Sar Interferogramsmentioning
confidence: 99%